Adsorpsi Surfaktan Nonionik Alkil Poliglikosida pada Antar muka Fluida-Fluida - Adisalamun, Adisalamun; Mangunwidjaja, Djumali; Suryani, Ani; Sunarti, Titi Candra; Arkeman, Yandra (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2012)
Nonionic surfactants have been used extensively in various industrial applications such as cleaning, personal care, crop protection, paint and coating, textile finishing, emulsion stabilization, food and leather processing. In this study, we have studied the adsorption of three nonionic surfactants of alkyl polyglycoside, namely commercial APG from Cognis and APG produced from glucose as well as APG synthesized from sago starch, at fluidfluid interfaces. The variation of surface and interfacial tension with the concentration of surfactant in the bulk was studied, and the data were fitted using a surface equation of state derived from the Langmuir isotherm. The agreement between ?(c) data and Langmuir isotherm model was very good.Keywords: adsorption, air/water interface, interfacial tension, surface tension